PROTOTIPE SISTEM PENGAMBILAN KEPUTUSAN RISIKO HIPERTENSI MENGGUNAKAN METODE PROFILE MATCHING - Nurul Washil Alqornie (2020)
Currently, technological developments in the era of globalization are moving very rapidly, therefore we must keep abreast of its developments, especially in the field of health. Hypertension is a health problem that is the main focus globally, because there are still many people who are not aware of the dangers of hypertension. It's good we know how risky we are to the dangers of hypertension. This research tries to make a prototype application to estimate the risk factors of someone experiencing hypertension. By using the Profile Matching method as a system design and Prototype method as a system development. The system design using the Profile Matching method has several stages, namely, determining GAP mapping variables, selecting candidates, calculating the results of GAP mapping, calculating the weight of GAP mapping, calculating and grouping core factors and secondary factors, and calculating the total value of each aspect. And obtain results that can provide information that a person can be predicted to have a risk of hypertension based on available variables